SURVEI KONDISI FISIK ATLET PUTRA USIA 14-16 TAHUN PB. REMAJA KABUPATEN JOMBANG - CATUR MAGALHAES, DANIEL Catur (Jurnal Prestasi Olahraga, 2013)
Sports development in the world in recent years has been greatly decreased, especially for improving achievement. One way to be taken in an attempt to improve performance by doing coaching badminton. Coaching can be done with the Badminton Association (PB), with the Badminton Association can discover talented athletes. The facilities and infrastructure that support the implementation of the exercise. Physical condition is a very important element, in almost all sports. All elements of the physical conditions must be developed to its full potential to perform a lethal punch and footwork that can reach all corners of the field. This research is descriptive quantitative approach. In this study, the population was five male badminton players of PB. Remaja. In accordance with the results of the calculation of the data obtained to determine the state of the physical conditions (dependent variable) PB. Remaja male athletes it can be summed up as follows: (1) arm muscle endurance, 100% PB. Remaja badminton player includes the category of "Less". (2) From the results of abdominal muscle strength tests, the results of 60% of athletes PB. Remaja included in the category of "less" and 40% of the category "Poor". (3) From the agility test results obtained by 80% of athletes PB. Remaja included in the category of "Excellent" and 20% to the category of "Good". (4) From the results of the speed test athletes earned 20% PB. Remaja included in the category of "less" and 80% in the category of "Poor". (5) From the test results obtained by 20% jump straight PB. Remaja athletes included in the category of "less" and 80% in the category of "Poor". (6) From the test results obtained 100% flexibility PB. Remaja athletes included in the category of "Poor". (7) From the test results obtained by the balance of 80% of athletes PB. Remaja included in the category of "Excellent" and 20% in the category of "Less". (8) From the test results obtained by 40% of athletes MFT PB. Remaja included in the category of "Medium" and 60% in the category of "Less". Then, according to the results of analysis and physical condition in accordance with the norms of each test item, the overall average physical condition of male athletes PB. Remaja age 14-16 years old is in category "Less". Keywords: Physical Condition, Male and Badminton